1997
DOI: 10.1002/srin.199700543
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning of austenite by hot working of microalloyed forging steels

Abstract: On four grades of medium carbon V‐bearing steels with additional Ti and Nb microalloying hot deformation tests were conducted as a simulation of hot forging. The aim of the study was to suggest general guidelines for the design of deformation patterns and cooling conditions of austenite. Both the resulting flow stresses and the strengthening/softening behaviour were taken into consideration. The maximum flow stresses appear to be insensitive both to the variation of microalloying and to the design of the defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…There are many researches conducted on the effect of chemical composition, forging temperature and post-forging cooling conditions. The effect of deformation temperature has been investigated and it is shown that decreasing the deformation temperature leads to the refinement of the prior austenite grains, which refines the final microstructure (Gonzalez-Baquet et al, 1997;Jahazi and Eghbali, 2001). Also, various cooling strategies have been applied to modify the microstructure and mechanical properties of these steels (Madariaga and Gutirrez, 1998;Sankaran et al, 2003;Nussbaum et al, 1998;Gűndűz a and Cochrane, 2005 to improve the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…There are many researches conducted on the effect of chemical composition, forging temperature and post-forging cooling conditions. The effect of deformation temperature has been investigated and it is shown that decreasing the deformation temperature leads to the refinement of the prior austenite grains, which refines the final microstructure (Gonzalez-Baquet et al, 1997;Jahazi and Eghbali, 2001). Also, various cooling strategies have been applied to modify the microstructure and mechanical properties of these steels (Madariaga and Gutirrez, 1998;Sankaran et al, 2003;Nussbaum et al, 1998;Gűndűz a and Cochrane, 2005 to improve the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of microstructures in microalloyed steels can be obtained depending on the deformation rate and temperature, cooling rate, as well as chemical composition [4][5][6]. The effect of deformation temperature has been investigated and it is shown that decreasing the deformation temperature leads to the refinement of the prior austenite grains, which in turn refines the final microstructure [2,7]. Ductility and toughness show a significant increase with a reduction in finishing temperature [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a decrease in the final deformation temperature led to a finer grain size (beneficial for toughness) and also promoted the formation of ferrite. [3,4,5] The present investigation forms a part of an attempt to improve the tensile properties and the fatigue resistance of the automotive grade microalloyed steel 38MnSiVS5 through thermomechanical processing to produce a F-B-M microstructure. [6][7][8][9] Here an attempt was made to optimize the parameters (finish forging temperature, quenching temperature, annealing temperature and time) of the TSCA treatment.…”
Section: Introductionmentioning
confidence: 99%